Oxaliplatin induces drug resistance more rapidly than cisplatin in H69 small cell lung cancer cells - STORDAL, BRITTA KRISTINA (Springer, 2006)
Cisplatin produces good responses in solid tumours including small cell lung cancer (SCLC) but this is limited by the development of resistance. Oxaliplatin is reported to show activity against some cisplatin-resistant cancers but there is little known about oxaliplatin in SCLC and there are no reports of oxaliplatin resistant SCLC cell lines. Studies of drug resistance mainly focus on the cellular resistance mechanisms rather than how the cells develop resistance. This study examines the development of cisplatin and oxaliplatin resistance in H69 human SCLC cells in response to repeated treatment with clinically relevant doses of cisplatin or oxaliplatin for either 4 days or 2h. Treatments with 200ng/ml cisplatin or 400ng/ml oxaliplatin for 4 days produced sublines (H69CIS200 and H69OX400 respectively) that showed low level (approximately 2-fold) resistance after 8 treatments. Treatments with 1000ng/ml cisplatin or 2000ng/ml oxaliplatin for 2h also produced sublines, however these were not stably resistant suggesting shorter treatment pulses of drug may be more effective. Cells survived the first five treatments without any increase in resistance, by arresting their growth for a period and then regrowing. The period of growth arrest was reduced after the sixth treatment and the H69CIS200 and H69OX400 sublines showed a reduced growth arrest in response to cisplatin and oxaliplatin treatment suggesting that "regrowth resistance" initially protected against drug treatment and this was further upregulated and became part of the resistance phenotype of these sublines. Oxaliplatin dose escalation produced more surviving sublines than cisplatin dose escalation but neither set of sublines were associated with increased resistance as determined by 5-day cytotoxicity assays, also suggesting the involvement of regrowth resistance. The resistant sublines showed no change in platinum accumulation or glutathione levels even though the H69OX400 subline was more sensitive to buthionine sulfoximine treatment. The H69CIS200 cells were cross-resistant to oxaliplatin demonstrating that oxaliplatin does not have activity against low level cisplatin resistance. Relative to the H69 cells, the H69CIS200 and H69OX400 sublines were more sensitive to paclitaxel and taxotere suggests the taxanes may be useful in the treatment of platinum resistant SCLC. These novel cellular models of cisplatin and oxaliplatin resistant SCLC will be useful in developing strategies to treat platinum-resistant SCLC.
PUBLISHED
Keywords: Cisplatin; Oxaliplatin; Cellular Response; SCLC; Small Cell Lung Cancer; Drug Resistance